2016
DOI: 10.1016/j.molcel.2016.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hippo Pathway Components by Gene Inactivation

Abstract: SUMMARY The Hippo pathway is important for regulating tissue homeostasis and its dysregulation has been implicated in human cancer. However, it is not well understood how the Hippo pathway becomes dysregulated because few mutations in core Hippo pathway components have been identified. Therefore, much work in the Hippo field has focused on identifying upstream regulators, and a complex Hippo interactome has been identified. Nevertheless, it is not always clear which components are the most physiologically rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
232
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(252 citation statements)
references
References 45 publications
13
232
4
3
Order By: Relevance
“…Pathological Yap activation is involved in the initiation and progression of various cancers, including pancreatic cancer, by promoting programs essential for tumorigenesis, such as proliferation, survival, stemness, epithelial-to-mesenchymal transition and metastasis programs (Yu et al, 2015; Zanconato et al, 2016b). However, while dysregulation of the Hippo pathway is a key event in many tumor types, mutations in Hippo pathway components themselves are rare, and the mechanisms that liberate Yap during tumorigenesis remain incompletely understood, underscoring the critical need to identify upstream regulators of this pathway (Plouffe et al, 2016; Zanconato et al, 2016b). Our results show that mouse tumors harboring complete p53 inactivation display significantly enhanced active nuclear Yap, suggesting that the wild-type p53 is key for negatively regulating Yap activity in PDAC and in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological Yap activation is involved in the initiation and progression of various cancers, including pancreatic cancer, by promoting programs essential for tumorigenesis, such as proliferation, survival, stemness, epithelial-to-mesenchymal transition and metastasis programs (Yu et al, 2015; Zanconato et al, 2016b). However, while dysregulation of the Hippo pathway is a key event in many tumor types, mutations in Hippo pathway components themselves are rare, and the mechanisms that liberate Yap during tumorigenesis remain incompletely understood, underscoring the critical need to identify upstream regulators of this pathway (Plouffe et al, 2016; Zanconato et al, 2016b). Our results show that mouse tumors harboring complete p53 inactivation display significantly enhanced active nuclear Yap, suggesting that the wild-type p53 is key for negatively regulating Yap activity in PDAC and in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has not been addressed in the in vitro studies already mentioned (Dethlefsen et al, ; Kim et al, ; Yu et al, ). For instance, whereas Lats1/2 and YAP activity can be directly regulated bypassing Mst1 (Plouffe et al, ; Wang et al, ; Yu et al, ), it is unclear whether activation of the Hippo pathway by β‐adrenoceptor stimulation involves Mst1 in the heart. It is also unknown what are the downstream target genes that are regulated by the β‐adrenoceptor‐Hippo signalling pathway and contribute to the development and worsening of heart disease.…”
Section: Activation Of β‐Adrenoceptors Upregulates Gal‐3 Expression Imentioning
confidence: 99%
“…A large number of studies have shown increased expression and/or nuclear accumulation of YAP and TAZ in a wide range of cancers, supporting the notion that disruption of Hippo signalling contributes to tumorigenesis . Surprisingly, however, mutations in genes coding for Hippo pathway effectors are infrequent, suggesting that YAP and TAZ expression in cancer cells is often altered via indirect mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…The study of YAP and TAZ regulation in cancer has therefore expanded beyond the canonical Hippo pathway and its core kinases (MST1/2 and LATS1/2) to include crosstalk with multiple signalling pathways such as MARK, Wnt, TGFβ/BMP, GPCR, PI3K‐mTOR, Notch, Hedgehog, mevalonate, AR and hypoxia signalling. The upstream and downstream regulatory components of the latter pathways can affect YAP and TAZ levels and activity via a number of mechanisms, thereby contributing to cancer progression . Hippo pathway activity can also be altered by other mechanisms in cancer cells, including copy‐number changes, loss of heterozygosity and epigenetic silencing .…”
Section: Discussionmentioning
confidence: 99%